1979
DOI: 10.1136/gut.20.6.526
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of maintenance cimetidine treatment in healed duodenal ulcer: short and long-term effects.

Abstract: SUMMARY Forty-two patients with endoscopically diagnosed duodenal ulcer were studied in a double-blind trial after their ulcers had been healed with cimetidine. Cimetidine was effective in preventing relapse, only five of the 20 patients allocated to cimetidine 400 mg twice daily relapsing during the six months' treatment, compared with 16 of the 22 on placebo treatment (p < 0.01). Cimetidine was safe in the dosage and duration used, no symptomatic, haematological, or biochemical abnormalities occurring during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…The 60% endoscopic relapse rate 1 year after discontinuation of treatment in patients in our study who had healed initially on cimetidine is similar to results of other trials [11,12], Although the difference between this figure and the lesser relapse rate of 47% in patients healing on TDB does not reach sta tistical significance, the trend is similar to another study in which a significantly smaller relapse rate at 1 year in patients who healed on TDB than in those who healed on cime tidine was shown [13], This difference may be related to improvement of the ultrastruc ture of the duodenal mucosa after treatment with TDB [14], However, a more recent re port [15] has shown a recurrence rate at 1 year of 75% irrespective of whether the ini tial healing was with cimetidine or TDB. The fact that 5 of the 6 patients in our study who required both treatments before healing re lapsed, suggests that they had severe duode nal ulcer disease.…”
Section: Discussionsupporting
confidence: 78%
“…The 60% endoscopic relapse rate 1 year after discontinuation of treatment in patients in our study who had healed initially on cimetidine is similar to results of other trials [11,12], Although the difference between this figure and the lesser relapse rate of 47% in patients healing on TDB does not reach sta tistical significance, the trend is similar to another study in which a significantly smaller relapse rate at 1 year in patients who healed on TDB than in those who healed on cime tidine was shown [13], This difference may be related to improvement of the ultrastruc ture of the duodenal mucosa after treatment with TDB [14], However, a more recent re port [15] has shown a recurrence rate at 1 year of 75% irrespective of whether the ini tial healing was with cimetidine or TDB. The fact that 5 of the 6 patients in our study who required both treatments before healing re lapsed, suggests that they had severe duode nal ulcer disease.…”
Section: Discussionsupporting
confidence: 78%
“…The same older literature showed that long‐term maintenance treatment with an H 2 ‐RA reduced ulcer recurrences to about 20–30% over 12 months, compared to background recurrence rates of around 70–90% per annum on placebo 56–58 . For maintenance, also, PPIs have been shown to be more effective than H 2 ‐RAs 55 .…”
Section: Management Of Non‐helicobacter Pylori Non‐steroidal Anti‐inmentioning
confidence: 98%
“…A long duration of the disease was re ported to slow healing [14,22,49] and to favor relapses [44,50], but in the majority of studies, no unfavorable effect on healing [ 17-19, 30, 32, 33,48, 51 ] and relapse [1,35,42,48,51,53] was observed. Similarly, some studies described slow healing [4,8] and a high relapse rate in males [54], but a major ity of studies was unable to confirm this [1,14, 18, 29, 30, 33, 35, 46-48.…”
Section: Discussionmentioning
confidence: 99%